PREFERENSI LABA JUAL BELI DALAM EKONOMI ISLAM - Rahmad (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2021)
Buying and selling is part of the activities muamalah arranged in order of the Islamic legal system. Problems that are considered vital in the sale and purchase of which is about taking advantage. In particular, in Islam is not set what percentage of profits that may be taken, but the teachings of Islam emphasizes making profits in line with the guidance of Sharia, which gains on an item should be obtained in a manner that is ethical same pleasure pleasure and not oppress others